Pelvic Exenteration for Recurrent Rectal Cancer: A Single Institution Experience - Serdar Culcu; Cemil Yüksel; Mahmut Onur Kültüroğlu; Fatih Göksel; Eda Güner; Bülent Aksel; Lütfi Doğan (Turkish Journal of Colorectal Disease, 2021)

(untitled)
Aim:Rectal cancer is an important cause of cancer-related deaths worldwide (1-2). Although rectal cancers can be diagnosed earlier nowadays due to the development of screening programmes, 18% of patients have a locally advanced stage at the time of diagnosis (3). Despite the improvements in total mesorectal excision and oncological treatments, the locoregional recurrence rates vary between 6-10% in rectal cancer patients (4-5).Method:The data of patients who underwent pelvic exenteration for recurrent rectal cancer in our clinic between January 2015 and December 2019 were retrospectively analysed.Results:It was found that the patients with lymphovascular invasion (LVI) and perineural invasion (PNI) showed statistically poor survival rates (p=0.038/0.022). Two of the patients had a positive surgical margin and two others had a positive radial margin. There was no statistically significant difference between surgical margin positivity and prognosis (p>0.05). The mean number of metastatic lymph nodes was 4.0 (0-12), and the total number of lymph nodes was 12.35 (2-27). There was no statistically significant difference between patients with lymph node metastasis in terms of survival (p=0.079). Seven of the patients (41.1%) received systemic treatment before the surgery. It was statistically determined that the patients who received this treatment showed better survival rates (p=0.045).Conclusion:It was found that pelvic exenteration had a positive effect on survival and local recurrence in recurrent rectal cancer, and that neoadjuvant therapy increased survival rates.